An Analysis Of Language Style Used By Main Character In “Keeping Mum” Movie - Aryndra, Toby; Skolastika, I Made Perdana (Journal of Language and Applied Linguistics, 2025)
In this study, language style was examined as it is used in the film "Keeping Mum," which illustrates how language style is employed in society. The varieties of language styles employed in the film "Keeping Mum" and the factors influencing the choice of language style in the "Keeping Mum" movie are the two issues that need to be resolved in the study. The theoretical foundation of this study is based on Joos (1967), who identified five different language styles: the frozen style, the formal style, the consultative style, the casual style, the intimate style, and according to Holmes (1992) The participant, setting, topic, and function are the four criteria used to select linguistic variety. The study's finding that there are 20 data points on the different language styles and elaborate factors influencing the choice of language style that been used in “Keeping Mum” movie and intimate style is the mostly language style used by the characters with percentage is about 40%.